IMPACT OF CHANGES IN THE FUNCTION OF THE CATUSPATHA ELEMENTS ON SOCIO-ECONOMIC CONDITIONS OF UBUD TRADITIONAL VILLAGE, KELURAHAN OF UBUD - Dewi, Putu Sri Agastina; Saraswati, Anak Agung Ayu Oka; Agusintadewi, Ni Ketut (ASTONJADRO, 2022)
In its literal sense, catuspatha contains sacred value, function, and its own meaning. In the context of Balinese culture catuspatha as the centre of a kingdom contains four constructuve elements that are adjusted to the desa kala, patra, in the respective regions. Meanwhile in the context of Hinduism with the changes within the system it is not possible tha in this era catuspatha will undergo functional change. The purpose of this research is to know the impact of socio-economic changes in the functions of the catuspatha elements of Ubud traditional village. To achieve this goal it is done with observations and interviews related to the catuspatha element forming. Also cross-check based on the literature and results of previous research. The study used qualitative-rationalistic methods with interactive data models miles and Huberman to discuss spatial changes in the past and present. The results derived from this research are the elements of catuspatha has undergone a change both in function and physically in the last few years because it adjusts the region and needs of the community and so that the land function is the result of positive and negative impacts in terms of socio-economic.